IMPROVING THE KNOWLEDGE AND SKILLS OF CHILDREN IN ORPHANAGES ABOUT ENVIRONMENTAL HEALTH AND PREVENTION OF FREE SEX FROM AN EARLY AGE - Hamdiah; Sutriani; Muhammad Multazam; Em Yusuf Iis; Jumadiah; Rusydi Abubakar (RADJA PUBLIKA, 2024)
Environmental health and free sex issues are important concerns in the context of sustainable development. Children in orphanages as part of a vulnerable group need to be equipped with knowledge and skills to face these challenges. This study aims to analyze strategies to improve the knowledge and skills of children in orphanages related to environmental health and early prevention of free sex. By using participatory methods and an education-based intervention approach, this study succeeded in improving children's understanding of these issues. These findings provide strategic recommendations for orphanage managers, the government, and related institutions to support the development of healthier and more empowered children.